CONCEPT & UTILITY OF GANGADHAROKTA NYAYAS W.S.R TO VIMANASTHANA (CAHIERS MAGELLANES-NS, 2024)
To understand the basic principles, Achary’s adopted various methods to make common individual to understand the shastra (science). One of the most important application is Nyaya (maxim) in the science.A general guideline or logical explanation that helps people understand different topics is known as the Nyaya.Loukika Nyaya and Shastriya Nyaya are the two varieties of nyayas. Most often, the Granthakaras proposed the ShastriyaNyayas by utilizing the essence and meaning of Loukika Nyaya.the ShastriyaNyayas were explained by the Granthakaras. Ayurveda acharyas found it as an easiest method for the clarification of the views what they want to put forth in theirsutras. Subsequently, the commentators on these sutras incorporated several Nyayasto explore the exact meaning of the actual verses.The Ayurvedic Acharyas used these Nyayas to explain the Sutra, Nidana, Vimana & Chikitsa, etc. To ensure that the Shastra is easily understood, it is vital to distinguish all of these Nyayas in one place, with illustrations. This is an attempt to investigate the Nyayas stated in Ayurveda for the purpose of simplifying the topic.